WEARABILITY OF METAL-POLYMERIC TRIBOSYSTEMS UNDER LOW-FREQUENCY VIBRATIONAL LOADING - Vadim A. Kokhanovskiy; Sergey I. Ivanov; Natalia G. Snezhina (Advanced Engineering Research, 2011)
The experimental results of the wearability of metal-polymeric tribosystem with the composite coverage under dynamic loading are presented.